Overview of the Covid-19 Patient Nursing Diagnosis - Nurhidayatun; Abdul Aziz (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2020)
Covid-19 is a pneumonia caused by coronavirus, very fast transmission. This study aims to descriptions nursing diagnosis in covid-19 patients. This is a descriptive study uses quantitative methods. The sampling technique used is consecutive sampling with total samples are 240 medical records of covid-19 patients undergoing treatment at Fatmawati Hospital, both suspected, probable, and confirmed cases. The results showed that nursing diagnoses that often appeared in Covid-19 patients were the risk of infection (spread), ineffective airway, acut pain, anxiety, and the risk of nutritional deficits. The results of this study can be used for the hospital in making Covid-19 Nursing Care Guidelines, and for nurses in increasing their competences in care covid-19 patients.